Impact of screen time on language development and sleep patterns in children: An observational cohort study - Rajasekhar Reddy,; SOVS Satish Reddy, (Asian Journal of Medical Sciences, 2025)
Background: Language development is a crucial aspect of a child’s growth, particularly during the formative years when cognitive and communication skills are rapidly evolving. Screen time exposure has been linked to developmental challenges in children. Aims and Objectives: This study aimed to explore the relationship between screen time and language development in children aged 6 years, with a specific focus on the role of screen content, sleep patterns, and socioeconomic factors. Materials and Methods: An observational cohort study was conducted over 12 months among 300 children enrolled in local schools in Nandyal. Screen time, sleep duration, and language development scores were assessed using standardized tools. The impact of screen content (educational, entertainment, and gaming) and socioeconomic status on language development was also evaluated. Statistical analyses included correlation and regression tests. Results: The average daily screen time was 3.5±1.2 h, increasing with age. Language development scores were inversely correlated with screen time (r=−0.62, P<0.001), with younger children (6–8 years) being most affected (r=−0.68, P<0.001). Children with screen time <2 h/day had higher language scores (82.7±10.2) than those with >4 h/day (68.9±11.8). Sleep duration decreased with higher screen time, mediating 25% of the adverse impact on language scores. Educational content positively influenced language scores (80.5±9.7), while gaming had the lowest scores (70.2±11.6). Socioeconomic status further modulated the relationship, with the strongest negative effects observed in low-income groups (β=−0.75, P<0.001). Conclusions: Excessive screen time negatively impacts language development and sleep in children, with younger age groups and low socioeconomic status being the most vulnerable. Limiting screen time and promoting educational content may mitigate these effects.